FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN ELEKTRIKAL PADA PEKERJA ELEKTRIK: LITERATURE REVIEW - Bintang Dwi Putro; Doni Hikmat Ramdhan (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Electrical accidents have a direct impact on workers' health conditions, production losses and losses experienced by companies due to loss of assets when work accidents occur. Accidents that occur are caused by several factors, which by knowing these factors, can provide relevant information regarding the causes of the occurrence of an electrical accident so that workers can prevent it before it happens. The research was carried out using the